Post-Apocalyptic Optimism: Utopia as a Mindset in Octavia. E Butler’s Parable of the Sower - Ms. Amal ARAAR, Ms. Sabrina DJEBBAR (My University, 2020)
Abstract Octavia Butler’s Parable of the Sower is a major work that tackles predictions about the near future that are not promising. However, the optimistic vision is highly apparent through the character of Lauren and her belief system “Earthseed” that calls for new possibilities; for instance, a new life across the space and the settlement of “Acorn” as a new community with a new world order. This project intends to examine utopianism within the novel, as hope is one significant feature of the genre of utopia. Additionally, there is a concern to develop a bridge between the black theology and the religious tendency in this literary work; as both see the world through a hopeful eye and seek to alter realities of hopelessness. The protagonist “Lauren Oya Olamina” is a significant character whose neurological disorder “Hyperempathy” shapes her way in dealing with the outer world. Her character, as a case study, is crucial for tracing an understanding of the futuristic utopian vision, a vision that is determined by optimism. Therefore, it is tended to be studied by applying the psychoanalytic theory.
Keywords: Key words: Post-apocalyptic, optimism, utopia, dystopia, hope, Parable of the Sower.